2019
DOI: 10.3727/096504018x15208986577685
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Suppresses Teratoma Cell Growth and Induces Cell Apoptosis via Inhibiting Bcl-2

Abstract: Luteolin, which is found in plant foods, has a range of therapeutic applications. In order to examine the potential roles of luteolin in ovarian teratocarcinoma, the human ovarian teratocarcinoma cell line PA-1 was selected for functional experiments in vitro and in vivo. We demonstrated that luteolin inhibited the proliferation and colony formation of PA-1 cells in vitro. The flow cytometry results suggested that luteolin induced apoptosis of PA-1 cells in a dose-dependent manner. Immunofluorescence and qRT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Luteolin (3′, 4′, 5, 7‐terahydroxyflavone) is a common effective dietary flavonoid that is present in fruits, vegetables, and medicinal herbs (Liu, Xu, Yan, Cheng, & Liu, ; Song et al, ). Furthermore, accumulating evidences have suggested that luteolin possesses multiple pharmacological activities such as anti‐inflammation, anti‐hypertension, antioxidant, and antitumor, which are also supposed to be the basis of these biological properties (Aziz, Kim, & Cho, ; Cui et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Luteolin (3′, 4′, 5, 7‐terahydroxyflavone) is a common effective dietary flavonoid that is present in fruits, vegetables, and medicinal herbs (Liu, Xu, Yan, Cheng, & Liu, ; Song et al, ). Furthermore, accumulating evidences have suggested that luteolin possesses multiple pharmacological activities such as anti‐inflammation, anti‐hypertension, antioxidant, and antitumor, which are also supposed to be the basis of these biological properties (Aziz, Kim, & Cho, ; Cui et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As defective apoptosis is one of the preponderant causative elements for the occurrence and development of diverse malignancy, stimulation of cell apoptosis is considered a common mechanism of anticarcinogen (Sun, Yang, et al, 2022). As been seen throughout an investigation with respect to the potential roles of luteolin in ovarian teratocarcinoma, these dietary components dampened the proliferation and colony formation of PA‐1 cells in vitro and in vivo, which the mechanism intimately related to regulating the proportion of Bcl‐2/Bax (Liu et al, 2019). Molecular biology studies have shown that circular RNAs (circRNAs) circ_0000190 were upregulated in lung cancer cells and tissues.…”
Section: Therapeutic Actions In Cancermentioning
confidence: 98%
“…LUT inhibited tumor stemness and metastasis potential in PC and OC by targeting Wnt (Han et al, 2018) and PPP2CA/YAP (Li, Hu, et al, 2023) signaling pathways. It downregulated Bcl‐2, MMP2, MMP3, and MMP9 expressions, hindering teratoma progression (Liu et al, 2019). LUT regulated the PI3K/AKT pathway, inhibiting villus cancer cell proliferation (Lim et al, 2016) and inducing apoptosis.…”
Section: Bioactivities Of Lutmentioning
confidence: 99%